Food and Zinc Intake, and Determinant of Zinc Status among Pregnant Women in Leuwiliang and Cibungbulang Sub-Districts, District of Bogor - Aslis Wirda Hayati; . Hardinsyah; . Rimbawan (Forum Pasca Sarjana, 2002)
The objectives of this study were to analyze zinc status, nutrient dietary quality, zinc content, zinc intake, determinant of zinc status and implications for preventing zinc deficiency among pregnant women living in Leuwiliang and Cibungbulang sub-districts, district of Bogor. The research used base line data of 252 pregnant women from previous study entitled "Effect of Multi-nutrients Fortificated Food Supplement for Pregnant Women and Child Growth and Development in Leuwiliang and Cibungbulang". Additional data collected were local food potency, zinc content of 17 foods, and formal and nonformal local leaders opinion on future institution programs related to nutrition and health.Logistic regression was applied for determinants analysis.